The five-factor model in schizotypal personality disorder - Gurrera, Ronald J. (2005)
Studies of the five-factor model of personality in schizotypal personality disorder (SPD) have produced inconsistent results, particularly with respect to openness. In the present study, the NEO-FFI was used to measure five-factor personality dimensions in 28 community volunteers with SPD and 24 psychiatrically healthy individuals. Standard multivariate statistical analyses were used to evaluate personality differences as a function of diagnosis and gender. Individuals with SPD had significantly higher levels of neuroticism and significantly lower levels of extraversion, agreeableness and conscientiousness than those without SPD. Female, but not male, SPD subjects had significantly higher openness levels than their healthy counterparts, and this gender-specific group difference persisted when SPD symptom severity was statistically controlled. These findings suggest that gender-associated differences in openness may account for prior inconsistent findings regarding this dimension, and they further underscore the importance of examining gender effects in future studies of SPD.